Dream in the rhythm: visions of sound and spirit in the MoMa collection - Bonner, Grace Wales; Kuo, Michelle Y.; Liljergen, Dana; Museum of Modern Art (New York, N.Y.) (The Museum of Modern Art, 2023)

The fashion crossroad method: Political and epistemological practices - Costa, Carla; Casarin, Carolina; Júnior, João Dalla Rosa; de Olivera Santos, Heloísa Helena; Medrado, Mi (Sustainability Challenges in the Fashion Industry, 2023)

What is education in fashion? Reflecting on the coloniality of design techniques in the fashion design educational process - Ahmed, Tanveer (International Journal of Fashion Studies, 2022)

Terres frontalières = La frontera : La nouvelle mestiza - Anzaldúa, Gloria; Dufour, Nino S.; Soto Chacón, Alejandra (Cambourakis, 2022)

Why we can't have nice things: Social media's influence on fashion, ethics, and property - Phạm, Minh-Hà T. (Duke University Press, 2022)

Speaking with light: Contemporary indigenous photography - Rohrbach, John; Wilson, William James Erasmus; Amon Carter museum of American art; Denver art museum (Radius Books ; Amon Carter Museum of Art, 2022)

The fossil fuel industry's legacy of white supremacy - Pierre-Louis, Kendra (Sierra : The magazine of the Sierra Club, 2021)

Vistas of modernity decolonial aesthesis and the end of the contemporary - Vázquez, Rolando (Mondriaan Fund, 2021)

Transfeminismo o barbarie - Mayor, Aingeru (Kaótica Libros, 2020)

Zanele Muholi - Muholi, Zanele; Allen, Sarah; Nakamori, Yasufumi; Tate Modern; Maison européenne de la photographie; Martin-Gropius-Bau; Umeå universitet Bildmuseet (Tate publishing, 2020)

Trans studies en las Américas - Rizki, Cole (Duke University Press, 2020)

The new black vanguard: Photography between art and fashion - Sargent, Antwaun (Aperture Foundation, 2019)

The museum, decoloniality and the end of the contemporary - Vázquez, Rolando (The Future of the New: Artistic Innovation in Times of Social Acceleration, 2018)

Soul of a nation: Art in the age of black power - Godfrey, Mark; Whitley, Zoé; Cahan, Susan; Tate Modern; Crystal Bridges Museum of American Art; Brooklyn Museum of Art (Tate Publishing, 2017)

Théorie de la création: Philosophie et créativité - Savadogo, Mahamadé (Éditions l'Harmattan, 2016)

Sociología de la imagen: Miradas ch'ixi desde la historia andina - Rivera Cusicanqui, Silvia (Nociones Comunes, 2015)

Towards a decolonial critique of modernity: Buen vivir, relationality and the task of listening - Vázquez, Rolando (Capital, poverty, development, 2012)

Snap judgments: new positions in contemporary African photography - Enwezor, Okwui; International Center of Photography (Steidl : International Center of Photography, 2006)

Antifascist feminisms: forging a travesti-trans international - Rizki, Cole (Feminist Theory, 2025)

Autohistorias: penser avec Gloria Anzaldua - Anzaldúa, Gloria (Beaux-arts de Paris, 2024)

Composición y vivencia en la arquitectura de Rogelio Salmona - Aschner Rosselli, Juan Pablo (Universidad Nacional de Colombia : Universidad del Rosario, 2024)

La casa como manifiesto de Luis Barragán - Barragán, Luis; Ruy Sánchez, Alberto; Orellana, Margarita de; Luna, Sandra; DeVos, Whitney; Cornejo, Lucía (Artes de México, 2024)

Extraordinarely apotropaic - Dolce Stil Criollo (Sometimes Always, 2024)

La pisada del nandú: Río Paraná - Sacchi, Duen; De Santo, Mag; Museo de Arte Contemporáneo; Palau de la Virreina; Centro Cultural de la Memoria Haroldo Conti (Temblores Ediciones Museo de Arte Contemporáneo, 2024)

7 Steps Back/Forward/Aside (Gesturing Towards Decolonial Futures, 2023)

In our hands: Native photography, 1890 to now - Ahlberg Yohe, Jill; Grey Eagle, Jaida; Riley, Casey; Minneapolis Institute of Arts (Minneapolis Institute of Art, 2023)

Semiocapitalismo: Del producto marca, de la mercancía al signo/mercancía - Caro, Antonio (Sb, 2023)

Juan Pablo Echeverri - Echeverri, Juan Pablo (James Fuentes Press, 2023)

Arctic amazon: Networks of global indigeneity - McMaster, Gerald; Vincent, Nina (Goose Lane Editions ; Wapatah Centre for Indigenous Visual Knowledge, 2023)

Meryl McMaster: Nikihci-Âniskotâpân = Bloodline - McMaster, Meryl; Sainte-Marie, Buffy; Halfe, Louise Bernice; Milroy, Sarah; Campbell, Maria; Collection McMichael d'art canadien; Remai Modern; Musée d'art de Joliette; Magenta Publishing for the Arts (The Magenta Foundation, 2023)

Decolonial fashion ethnography: ‘Before yesterday’ method - Medrado, Mi (International Journal of Fashion Studies, 2023)

Decoloniality and fashion: RCDF 10th anniversary - Medrado, Mi (Decolonial Zine on Fashion, 2023)
The Decoloniality and Fashion e-zine celebrates the 10th anniversary of the Research Collective for Decoloniality and Fashion! Please complete this form to receive a FREE copy

Gore aesthetics: Chilean necroliberalism and travesti resistance - Rizki, Cole (Journal of Latin American Cultural Studies, 2023)

Aesthesic and epistemic restitution for the joy of life: Recalling earth, overcoming' the contemporary, knowing otherwise - Vázquez, Rolando (Errant Journal, 2023)

Pausing for thought: Lost and found - Cheang, Sarah (International Journal of Fashion Studies, 2022)

Decolonizing fashion [studies] as process - Cheang, Sarah; Rabine, Leslie; Sandhu, Arti (International Journal of Fashion Studies, 2022)

Creating african fashion histories: Politics, museums, and sartorial practices - Creating African Fashion Histories (Conference); Akou, Heather Marie; McGregor, JoAnn; Stylianou, Nicola (Indiana University Press, 2022)

Events of the social: Portraiture and collective agency : African photography from The Walther Collection - Dyangani Ose, Elvira; The Walther collection; Círculo de bellas artes; PHotoEspaña (The Walther Collection Books ; Steidl, 2022)

22 Años de miss fotojapón - Echeverri, Juan Pablo; Castella, Ana; Álvarez Luna, Pedro; Poveda Motta, Clemencia; Felipe Rodríguez, Daniel; Fórum Cultural Guanajuato Museo de Arte e Historia de Guanajuato (Gobierno del Estado de Guanajuato : Fórum Cultural Guanajuato, Museo de Arte e Historia de Guanajuato, 2022)

Conversations on decoloniality & fashion on ‘decolonial aestheSis and fashion’ - Research Collective for Decoloniality & Fashion (Youtube, 2022)

Manifiesto antirracista: Escrituras para una biografía inmigrante - Mijail, Johan (Editorial Fruta Bomba, 2022)

Defining defashion: A manifesto for degrowth - Niessen, Sandra (International Journal of Fashion Studies, 2022)

Jade Kuro: Ditching ‘the ideal’ narrative - Olowo-Ake, Oluwasola Kehinde (International Journal of Fashion Studies, 2022)

Mahila1 à la mode: The auntie-fit croqui - Sandhu, Arti (International Journal of Fashion Studies, 2022)

Critical practices talks #7 with Rolando Vázquez - Critical Practices Talks (YouTube, 2021)

Quechua 101 land back please - Bobby Sanchez (YouTube, 2021)

As we rise: Photography From the black atlantic - Cole, Teju; Sealy, Mark; Ikiriko, Liz; Brielmaier, Isolde; Montague, Kenneth; University of Toronto Art Museum; Polygon Gallery (Aperture, 2021)

Nous sommes un continent: correspondance mestiza - Dawson, Nicholas; Rosso, Karine (Triptyque, 2021)

Border theatrics - Dolce Stil Criollo (Sometimes Always, 2021)

Falling monuments, reluctant ruins: The persistence of the past in the architecture of apartheid - Judin, Hilton (Wits University Press, 2021)

Border garments: Fashion, feminisms, and disobedience - Martinez, Loreto (The Fashion Studies Journal, 2021)

Decoloniality and fashion in Brazil : Zine - Medrado, Mi (Decolonial zine on Fashion, 2021)

Chapeo - Mijail, Johan (Elefanta Editorial, 2021)

Santo Domingo is burning - Mijaíl, Johan (Lumpen Editorial, 2021)

Despadre: Masculinidades, travestismos y ficciones de la ley en la literatura peruana - Saona, Margarita (Gafas Moradas editorial, 2021)

Decolonizing the curriculum? Transformation, emotion, and positionality in teaching - Cheang, Sarah; Suterwalla, Shehnaz (Fashion Theory, 2020)

Curating fashion as decolonial practice: Ndwalane’s Mblaselo and a politics of remembering - de Greef, Erica (Fashion Theory, 2020)

Fashion and the phantasmagoria of modernity: An introduction to decolonial fashion discourse - Jansen, M. Angela (Fashion Theory, 2020)

Meryl McMaster: As immense as the sky - McMaster, Meryl; Watkins, Jonathan; Elmmer, Thomas; Lippard, Lucy R.; Nixon, Lindsay; Ikon Gallery (Ikon Gallery, 2020)

Fashion, its sacrifice zone, and sustainability - Niessen, Sandra (Fashion Theory: The Journal of Dress, Body & Culture, 2020)

Larger than memory: Contemporary art from indigenous North America - Pardue, Diana F.; Joyce, Erin; Taylor, Tobi; Paddison, Deborah; Heard Museum (Heard Museum, 2020)

Ch'ixinakax utxiwa: On practices and discourses of decolonisation - Rivera Cusicanqui, Silvia; Gago, Verónica (Critical South, 2020)

African cosmologies: Photography, time, and the other - Sealy, Mark; Evans, Steven; Fields, Max; Eyene, Christine; FotoFest (Schilt Publishing ; FotoFest, 2020)

Decolonizing fashion: Defying the ‘white man’s gaze’ - Jansen, Angela (Research Collective for Decoloniality & Fashion, 2019)

Rogelio Salmona: Un arquitecto frente a la historia - Albornoz Rugeles, Cristina; Salmona, Rogelio; Universidad de los Andes (Bogotá (Ediciones Uniandes, 2019)

Autonomia y diseno: La realizacion de lo comunal - Escobar, Arturo (UNIVERSIDAD DEL CAUCA, 2019)

Re-thinking luxury in the museum fashion exhibition - Lezama, Nigel (Luxury, 2019)

Ficciones patógenas - Sacchi, Duen; Preciado, Paul B. (Rara Avis Editorial, 2019)

Petro-masculinity: Fossil fuels and authoritarian desire - Daggett, Cara (Millennium, 2018)

Foreword : On pluriversality and multipolarity - Mignolo, Walter D. (Constructing the Pluriverse, 2018)

Introduction - Walsh, Catherine E.; Mignolo, Walter D. (On Decoloniality : Concepts, Analytics, Praxis, 2018)

Fashion history: A global view - Welters, Linda; Lillethun, Abby (Bloomsbury Academic, 2018)

Ethnicity - Baxter, Denise Amy; Cheang, Sarah (A Cultural History of Dress and Fashion in Age of Empire, 2017)

Recent histories: Contemporary African photography and video art - Chagas, Edson; Baumann, Daniela; Chuang, Joshua; Onabanjo, Oluremi C.; Walther Collection (The Walther Collection ; Steidl, 2017)

Rogelio Salmona: Un acuerdo tácito con la historia - Conenna, Claudio (Architectum Plus, 2017)

Racial plagiarism and fashion - Pham, Minh-Ha T. (QED: A Journal in GLBTQ Worldmaking, 2017)

Introduction - Craik, Jennifer; Jansen, M. Angela (Modern fashion traditions: negotiating tradition and modernity through fashion, 2016)

A reinvented vocabulary: Decoding the many dimensions of African design - Interview with Okwui Enwezor - Kries, Mateo; Klein, Amelie; Vitra Design Museum; Museo Guggenheim Bilbao; Centre de Cultura Contemporània de Barcelona (Making Africa: a continent of contemporary design, 2015)

Metalurgia en la América antigua teoría, arqueología, simbología y tecnología de los metales prehispánicos - Lleras Pérez, Roberto (Institut français d'études andines, 2015)

Con el corazón en la mano - Aterciopelados; Echeverri, Juan Pablo (2014)

Cuentos completos - Caicedo Estela, Andrés (Alfaguara, 2014)

Decolonial options and artistic/aestheSic entanglements: An interview with Walter Mignolo - Gaztambide-Fernández, Rubén (Decolonization: Indigeneity, Education & Society, 2014)

A world in common: Contemporary african photography - Bonsu, Osei; Makhubu, Nomusa; Bajorek, Jennifer; Iduma, Emmanuel; Colard, Sandrine (Tate, 2013)

Saturday night thriller y otros escritos - Campuzano, Giuseppe (Estruendomudo, 2013)

Decolonial aestheSis: Colonial wounds/decolonial healings - Mignolo, Walter; Vazquez, Rolando (Social Text, 2013)

Fernando Botero: Celebración - Botero, Fernando; Vargas Llosa, Mario; Botero, Lina; Museo de Bellas Artes de Bilbao (La Fábrica ; Museo de Bellas Artes de Bilbao, 2012)

¡Que viva la música! - Caicedo Estela, Andrés; Cohen, Bernard (Belfond, 2012)

Luis Barragán en su casa de Tacubaya: Naturalezas del límite - López Viso, Cruz (Edicións Espontáneas, 2012)

La casa de Luis Barragán: Un valor universal - Barragán, Luis; Alfaro, Alfonso; Garza Usabiaga, Daniel; Palomar, Juan; López Luz, Pablo; Moreno Guzmán, Alberto (Fundación BBVA Bancomer, 2011)

Interpreting “civilization” through dress - Niessen, Sandra (Berg Encyclopedia of World Dress and Fashion : West Europe, 2010)

A useful dream: African photography, 1960-2010 - Simon, Njami; Palais des beaux-arts (BOZAR Centre for Fine Arts : Silvana Editoriale, 2010)

Modernity, the greatest show one earth: Thoughts on visibility - Vázquez, Rolando (Borderlands e-journal, 2010)

Luis Barragán, 25 transparencias inéditas - Barragán, Luis; Riggen Martínez, Antonio (Mudito & Co, 2009)

Historia universal de la infamia - Borges, Jorge Luis (Pocket, 2008)

Le rapport de Brodie - Borges, Jorge Luis (Gallimard, 2008)

Museo travesti del peru - Campuzano, Giuseppe; University of Sussex Institute of Development Studies (Giuseppe Campuzano, 2008)

Rogelio Salmona: Tributo - Castro, Ricardo L.; Villegas Jiménez, Benjamín.; Salmona, Rogelio (Villegas Editores, 2008)

Clothing: A global history or, the imperialists' new clothes - Ross, Robert John (Polity, 2008)

L'Aleph - Borges, Jorge Luis (Galimard, 2007)

Poétique de la relation - Glissant, Edouard (Gallimard, 2007)

Coloniality and modernity/rationality - Quijano, Aníbal (Cultural Studies, 2007)

Botero: Abu Ghraib - Botero, Fernando; Ebony, David (Prestel, 2006)

Afterword: Reorienting fashion theory - Niessen, Sandra (Re-Orienting Fashion the Globalization of Asian Dress, 2003)